2019
DOI: 10.1111/1756-185x.13578
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide‐induced tolerogenic dendritic cells attenuated arthritis in experimental collagen‐induced arthritic mice

Abstract: Aim: Cumulative evidence has revealed that tolerogenic dendritic cells (tolDC) could relieve inflammation reactions in various autoimmune diseases. This study investigated the potential therapeutic application of vasoactive intestinal peptide (VIP)-induced tolDC (VIP-DC) on arthritis using collagen-induced arthritis (CIA) mice. Methods: Bone marrow cells were differentiated into dendritic cells (DC) using granulocyte macrophage colony-stimulating factor and interleukin (IL)-4. tolDC were induced by either VIP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Very interestingly, as also observed in human monocytes, 52 Tofa exposure does not prevent MHC‐II upregulation. The net result of such an altered phenotype would be the preservation of alloantigens presentation (Signal 1) with reduced Signals 2 and 3 (strengthening the effect of CTLA4‐Ig) and ultimately translating into a tolerogenic DC phenotype 56‐60 . We believe these regulatory effects contribute to the extension of transplant survival we observed.…”
Section: Discussionmentioning
confidence: 79%
“…Very interestingly, as also observed in human monocytes, 52 Tofa exposure does not prevent MHC‐II upregulation. The net result of such an altered phenotype would be the preservation of alloantigens presentation (Signal 1) with reduced Signals 2 and 3 (strengthening the effect of CTLA4‐Ig) and ultimately translating into a tolerogenic DC phenotype 56‐60 . We believe these regulatory effects contribute to the extension of transplant survival we observed.…”
Section: Discussionmentioning
confidence: 79%
“…In either case, the later administration in vivo of these cells produces Ag-specific Treg capable of inducing specific tolerance to naïve recipients. In this way, they cause the attenuation of symptoms of different animal models of autoimmune and/or inflammatory diseases, for example, in CIA arthritis, TNBS-induced colitis, EAE, sepsis, and spontaneous autoimmune peripheral polyneuropathy [177,[179][180][181][182]. In addition, in vitro studies with VIP have shown that it affects not only the phenotypic and functional maturation of DCs, but also the migration of these cells [183][184][185].…”
Section: Inducing Tolerogenic Dendritic Cellsmentioning
confidence: 99%
“…The net result of such an altered phenotype would be the preservation of alloantigens presentation (Signal 1) with reduced Signal 2 and 3 (strengthening the effect of CTLA4-Ig) and ultimately translating into a tolerogenic DC phenotype. [55][56][57][58][59] We believe these regulatory effects contribute to the extension of transplant survival we observed, and we are further investigating this mechanistic aspect.…”
Section: Discussionmentioning
confidence: 76%